Surface Engineering & Coating Technologies for Corrosion and Tribocorrosion Resistance - Sun, Yong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of the peer-reviewed papers published in the Special Issue "Surface engineering & coatings technologies for corrosion and tribocorrosion resistance" in the Materials journal. The Special Issue reprint aims to bring together the latest developments in this technologically, economically, and environmentally important area. It provides a forum for researchers to share their original work or insight reviews in this field.